Pengaruh Kecerdasan Logis-Matematis dan Kemampuan Berpikir Kritis terhadap Hasil Belajar Statistik Dasar Siswa Kelas VI SDN 07 Pinang Sebatang Barat - Reniviolina simanjuntak; Jesi Alexander Alim; Zetra Hainul Putra (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The purpose of this study was to determine the effect of logistical-mathematical intelligence and critical thinking skills on the learning outcomes of elementary school students in basic statistics. This study is based on the fact that most students still experience difficulties in mathematics, especially in understanding basic statistics material, which is indicated by low learning outcomes. This study used a quantitative approach with an ex post facto research type and correlational design. The study population was grade VI-A students at SDN 07 Pinang Sebatang Barat in the 2025/2026 academic year, with a sample of 30 students selected through a purposive sampling technique. The research instruments included a logistical-mathematical intelligence test and a critical thinking ability test, as well as a basic statistics learning outcome test. The results showed that (1) logistical-mathematical intelligence had a positive effect on students' basic statistics learning outcomes, (2) critical thinking ability had a positive effect on students' basic statistics learning outcomes, and (3) simultaneously, logistical-mathematical intelligence and critical thinking ability had a significant effect on basic statistics learning outcomes. Thus, it can be concluded that the combination of logistical-mathematical intelligence and critical thinking ability plays an important role in broadening students' insight into basic statistics material.